Harnessing Plant Power: A Review of Green-Biosynthesized Silver Nanoparticles for Improving Orange Postharvest Quality and Green Mold Resistance - Ali, Zulfiqar (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2025)
The increasing demand for fresh, organic produce has prompted the exploration of innovative methods to enhance post-harvest quality and combat diseases in fruits, particularly citrus. This review focuses on the green synthesis of silver nanoparticles (AgNPs) using plant extracts, which serve as both reducing and stabilizing agents, as a sustainable alternative to traditional chemical fungicides. The nanoparticles are characterized by their size, morphology, and stability using techniques such as UV-Vis spectroscopy, X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). The biogenic AgNPs demonstrated significant antifungal activity against Penicillium digitatum, the causative agent of green mold disease in oranges, effectively prolonging shelf life while maintaining the fruit's visual and nutritional quality. The synthesized nanoparticles exhibited stability and efficacy over extended periods, reducing weight loss and enhancing key quality parameters such as ascorbic acid content and titratable acidity. Despite these promising findings, the underlying mechanisms of AgNPs action and their interactions with pathogens at the molecular level remain inadequately understood. This review highlights the need for further research to elucidate these mechanisms, assess the environmental safety of AgNPs, and explore their potential applications across various crops. Ultimately, this study aims to contribute to sustainable agricultural practices by integrating eco-friendly solutions into post-harvest management strategies.